Perbandingan Abnormal Return, Trading Volume Activity dan Harga Saham Perbankan Sebelum dan Sesudah Merger dan Akuisisi - Marshanda Nurafriza; Isni Andriana; Kemas M. Husni Thamrin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine and analyze differences in Abnormal Return, Trading Volume activity and stock prices before and after the announcement of mergers and acquisitions in public listed banking companies on the IDX in the 2018-2022 period. The study population consists of 42 banking companies that have been listed on the Indonesia Stock Exchange. The purposive sampling method was used to select the sample, which eventually consisted of 11 banks that carried out mergers and acquisitions between 2018-2022. This study applies an event study with Wilcoxon signed rank test covering 30 days before 30 days after the announcement of mergers and acquisitions. The results of this study showed that of the 11 banks studied, only 1 bank had significant differences in abnormal variables and 6 banks had a significant difference in the trading activity volume variable and overall banking had a significant difference in the stock price variable. This research is expected to be used as reference material for future research and used for investment practitioners.